2019
DOI: 10.1002/pits.22282
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal disciplinary and achievement outcomes associated with school‐wide PBIS implementation level

Abstract: Positive behavioral interventions and support (PBIS) is a multitiered framework for behavioral support that is being increasingly implemented in schools. Although research has linked PBIS to improved student outcomes, less research is longitudinal and considers both academic and behavioral outcomes. This study examined the relationships between changes in school‐wide (i.e., Tier I) PBIS implementation level and changes in disciplinary and achievement outcomes over a 2‐year period. Participants included 85 Ohio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Several studies have shown the correlation between SWPBIS implementation and fewer suspensions and office discipline referrals (e.g., Bradshaw et al, 2010) and improved student prosocial behavior (e.g., Bradshaw et al, 2012). In a recent 2‐year longitudinal study on SWPBIS implemented in 85 schools from 31 Ohio school districts, James et al (2019) found a linkage between Tier 1 implementation fidelity and reductions in student problem behavior (out‐of‐school suspension rate), suggesting that improvement in implementation fidelity was related to reductions in student problem behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the correlation between SWPBIS implementation and fewer suspensions and office discipline referrals (e.g., Bradshaw et al, 2010) and improved student prosocial behavior (e.g., Bradshaw et al, 2012). In a recent 2‐year longitudinal study on SWPBIS implemented in 85 schools from 31 Ohio school districts, James et al (2019) found a linkage between Tier 1 implementation fidelity and reductions in student problem behavior (out‐of‐school suspension rate), suggesting that improvement in implementation fidelity was related to reductions in student problem behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Sufficiently powered studies with large enough samples of schools/agencies will allow significance testing of factors that facilitate or impede implementation at the school/agency level. Although large implementation studies of widely used education interventions (e.g., Positive Behavior Interventions and Supports; Horner & Sugai, 2015; James, Noltemeyer, Ritchie, Palmer, & Miami University, 2019) are valuable, implementation research of this nature is costly and typically requires resources that schools and intervention developers simply do not have. As web platforms increasingly become an integral component of educational interventions (Kimmons, 2020), evidence of implementation can be stored automatically in database logs of user activity, making implementation studies of this nature more practical.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of school-wide supports on student outcomes tend to be highest among at-risk or high-risk children (Bradshaw, 2013). Notably, a longitudinal study found disciplinary and achievement outcomes associated with prevention at the school-wide level when schools implemented universal supports with fidelity (James et al, 2019).…”
Section: Mtss and Bullying Preventionmentioning
confidence: 99%